Parental Knowledge on Breastfeeding: Contributions to a Clinical Supervision Model in Nursing - Reis Santos, Margarida (2015)
Abstract—Parental skills development in breastfeeding, not only eases the bonding and the maintenance of the process, but also, mirrors the excellence of nursing care. The study aims to assess parental knowledge concerning breastfeeding, in order to bring forth contributions for a clinical supervision model, which promotes the development of nursing skills.A quantitative and cross sectional study was conducted on a non-probability sample consisting of 135 recent mothers. The enquiry form applied allowed the assessment of parental skills on breastfeeding and in determining the conditions for the development of these skills. Most women (63%) provided information on the benefits of breastfeeding, 75% of the mothers did not show familiarity with strategies on how to continue breastfeeding. The study pointed to the existence of practices that impair the progress of acknowledgement on breastfeeding and contribute to early withdrawal, such as: delay in breastfeeding initiation, early introduction to infant formula, lack of nurses’ guidance and support on breastfeeding, during the post-partum period. Clinical supervision can be a means for the development of nursing skills allowing a widespread improvement of practices and rates (exclusivity and duration) of breastfeeding, boosting parent’s capacity, security, trust and satisfaction, which regards breastfeeding.